A Smart Photothermal Nanosystem with an Intrinsic Temperature‐Control Mechanism for Thermostatic Treatment of Bacterial Infections. Issue 44 (3rd October 2022) - Wang, Jiaxin; Hao, Boyi; Xue, Ke; Fu, Hao; Xiao, Minghui; Zhang, Yongxin; Shi, Linqi; Zhu, Chunlei
Abstract: Photothermal therapy (PTT) has attracted extensive attention in disease treatments. However, conventional photothermal systems do not possess a temperature‐control mechanism, which poses a serious risk to healthy tissues and/or organs due to inevitable thermal damage. Herein, a smart photothermal nanosystem with an intrinsic temperature‐control mechanism for thermostatic treatment of bacterial infections is reported. The smart photothermal nanosystem is constructed by loading a thermochromic material into a hollow‐structured silica nanocarrier, in which the thermochromic material is composed of naturally occurring phase‐change materials (PCMs), a proton‐responsive spirolactone, and a proton source. The resulting nanosystem shows strong near‐infrared (NIR) absorption and efficient photothermal conversion in solid PCMs but becomes NIR‐transparent when PCMs are melted upon NIR irradiation. Such an attractive feature can precisely regulate the photothermal equilibrium temperature to the melting point of PCMs, regardless of the variation in external experimental parameters. In contrast to conventional PTT with severe thermal damage, the reported smart photothermal nanosystem provides an internal protection mechanism on healthy tissues and/or organs, which remarkably accelerates the recovery of bacteria‐infected wounds. The smart photothermal nanosystem is a versatile PTT platform, holding great promise in the safe and efficient treatment of bacterial infections and multimodality synergistic therapy. Abstract : A smart photothermal nanosystem with an intrinsic temperature‐control mechanism is established for thermostatic treatment of bacterial infections. In contrast to conventional photothermal therapy with severe thermal damage, the reported smart photothermal nanosystem provides an internal protection mechanism on healthy tissues and/or organs, which remarkably accelerates the recovery of bacteria‐infected wounds.